-3(x-5)=-17

Simple and best practice solution for -3(x-5)=-17 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(x-5)=-17 equation:



-3(x-5)=-17
We move all terms to the left:
-3(x-5)-(-17)=0
We add all the numbers together, and all the variables
-3(x-5)+17=0
We multiply parentheses
-3x+15+17=0
We add all the numbers together, and all the variables
-3x+32=0
We move all terms containing x to the left, all other terms to the right
-3x=-32
x=-32/-3
x=10+2/3

See similar equations:

| 1/2x+3/10=2/5 | | 3(b–9)=18 | | 5s+16=116 | | 5(x+2)+16=2(x-2) | | 5a+8=3a-(8) | | 2500=16s^2+25 | | X÷3-3=x÷9+3 | | w2+5w+6=0 | | 9.7(0.4)^x=2 | | 3x-40=29 | | 5x+5=1/5x+29 | | 2x-10=6x-20 | | 5(4)+8=3x−2= | | F(x)=4-6x+2-1 | | 45x*9x=9x*45x | | 15-7m=6 | | 4(-63+7y)-3y=-4 | | 5x+8=3x−2= | | Y=(3)/(5x+7) | | -17x-14=82 | | -y-3*2=5 | | -y-3=5 | | -15x+19=15x-26 | | 5x+8=3x−2 | | ⅘x+⅙=8/3x-2 | | x+2=(3x+6)^(1/2) | | 3x-77=25 | | x+2(4x)=36 | | 3x+9x=-24 | | -8x(2+5x)-2(x+2)=120 | | 4(7x+18)^(1/2)=x | | -y+3*1=5 |

Equations solver categories